An investigation of the differential effects of leader behaviors on employee safety - Hoffmeister, Krista, author; Kraiger, Kurt, advisor; Rosecrance, John, committee member; Gibbons, Alyssa, committee member; Henry, Kim, committee member (Colorado State University. Libraries, 2012)
Leadership is frequently associated with positive safety outcomes such as improved perceptions of safety climate, increased safety behaviors, and decreased accidents and injuries. However, this research has mainly focused on the influence of general leadership on these safety outcomes. The present study sought to break down transformational and transactional leadership into their individual behavioral components and examine their unique influences on employee safety outcomes. From a sample of construction pipefitters and plumbers, results showed that idealized influence frequently explained the most variance in the safety outcomes, while individualized consideration and active management-by-exception were explained the least. Implications for leadership training and development are discussed.
Keywords: construction; safety; leadership